The landscape on industrial heritage interpretation. The ports - Leal del Ojo de la Cruz, Yaneli (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
In the second half of the 20th century, with the change in artistic ideals and the opening of patrimonial policies, industry was included in cultural heritage. However, industrial heritage still comes across some resistance and little visibility, which leads to the loss, degradation and mismanagement of many valuable assets and industrial sites. This article analyzes the conflictive factors on its interpretation, and finds in the comprehensive analysis of the cultural landscape the key to the fair valuation of industrial heritage. It presents the port landscape as an example of the interdependence between industry and landscape, which allows better to know its impact at the territorial, social, economic, political and cultural level. In summary, it explains the need to establish an open and flexible methodology based on landscape studies for efficient management, which should be characterized by interdisciplinarity to pursue various levels of heritage interpretation, and must be expand to communication and heritage education of contemporary society.